MENGUKUR KINERJA KEUANGAN DENGAN MENGGUNAKAN RASIO PROFITABILITAS DAN RASIO LIKUIDITAS DI PT BUKIT ASAM TBK PERIODE 2017-2021 - Raras Risia Yogasnumurti (Jurnal Manajemen, 2023)
ABSTRACT This study aims to determine the financial performance of PT Bukit Asam Tbk, namely by using ratio analysis in the form of profitability ratios and liquidity ratios. The data analyzed is the financial statements of PT. Bukit Asam Tbk in the form of a balance sheet and income statement from 2017 to 2021. The analytical tool used in this study is to use profitability ratios which include profit margin ratios, Return On Assets (ROA) ratios, and Return On Equity ratios ( ROE); as well as liquidity ratios which include the current ratio (Current Ratio) and the quick ratio (Quick Ratio). The results of the discussion show that the measurement of the financial performance of PT Bukit Asam Tbk based on the Cashmere theory for the 2017-2021 period can be said to be a company that is already good in terms of its liquidity ratio, while there are still 2 indicators that are not good in the profitability ratio, namely the ratio of Return On Assets (ROA). ) and Return On Equity (ROE) ratio. This is because in 2019 and 2020 the international economy was not doing well due to the COVID-19 pandemic so that PT Bukit Asam Tbk also had an impact and experienced a decrease in current assets, inventories and current liabilities. Keywords: Financial Performance, Profitability Ratios, Liquidity Ratios.